The association between stress, emotional states, and tinnitus: a mini-review - Patil, Jayaditya Devpal; Alrashid, Manar Abdulkarim; Eltabbakh, Ayah; Fredericks, Salim (Frontiers in Aging Neuroscience, 2023)
Extensive literature supporting the view of tinnitus induced stress in patients is available. However, limited evidence has been produced studying the opposite, that is, does stress cause tinnitus? The hypothalamus pituitary adrenal axis, one of the main neuroendocrine systems involved in stress response, is commonly disturbed in tinnitus patients. Patients with chronic tinnitus have been shown to develop abnormal responses to psycho-social stress, where the hypothalamus pituitary adrenal axis response is weaker and delayed, suggesting chronic stress contributes to the development of chronic tinnitus. The sympathetic branch of the autonomic nervous system also plays a major role in stress response and its chronic hyperactivity seems to be involved in developing tinnitus. Psycho-social stress has been shown to share the same probability of developing tinnitus as occupational noise and contributes to worsening tinnitus. Additionally, exposure to high stress levels and occupational noise doubles the likelihood of developing tinnitus. Interestingly, short-term stress has been shown to protect the cochlea in animals, but chronic stress exposure has negative consequences. Emotional stress also worsens pre-existing tinnitus and is identified as an important indicator of tinnitus severity. Although there is limited body of literature, stress does seem to play a vital role in the development of tinnitus. This review aims to highlight the association between stress, emotional states and the development of tinnitus while also addressing the neural and hormonal pathways involved.